Random deployment of wireless sensor networks: a survey and approach. (20th March 2014) - Senouci, Mustapha Reda; Mellouk, Abdelhamid; Aissani, Amar
Sensor placement is a fundamental issue in wireless sensor networks (WSNs). The sensor–positions can be predetermined to guarantee the quality of surveillance provided by the WSN. However, in remote or hostile sensor field, randomised sensor placement often becomes the only option. In this paper, we survey existing random node placement strategies. We categorise random placement strategies into simple and compound. An empirical study has been carried out yielding a detailed analysis of random deployment intrinsic properties, such as coverage, connectivity, fault–tolerance, and network lifespan.We also investigate the performance of a hybridisation of the simple diffusion model that places a large number of nodes around the sink and the constant diffusion that provides high coverage and connectivity rates. We show that such hybridisation ensures better performance. The obtained results give helpful design guidelines in using random deployment strategies.